Negative active material for secondary battery, method of preparing same, and lithium secondary battery including same

By forming Si/C composites with silicon-based coatings on carbon-based particles, the pretreatment step is used to improve the microwave absorption capacity of carbon-based particles, and the problems of electrical desorption and reversible capacity loss caused by volume changes in the silicon-based anode material during lithium embedding/deintercalation process are solved, and the uniform distribution of silicon nanoparticles and the improvement of lithium ion diffusion efficiency are achieved, which extends the battery life and reduces manufacturing costs.

CN119542369APending Publication Date: 2025-02-28ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411144093.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-28
Filing Date
2024-08-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The silicon-based negative electrode material causes volume changes during the lithium embedment/deintercalation process, resulting in electrical desorption and reversible capacity loss. It is difficult to uniformly form silicon nanoparticles when heated by microwaves, affecting the mechanical stability of the electrode and the life of the battery.

Method used

By forming a Si/C composite with a silicon-based coating on the carbon-based particles, the pretreatment step is used to improve the microwave absorption capacity of the carbon-based particles, inhibit coarseness and thinning of the silicon particles, and uniformly disperse the silicon nanoparticles by controlling the specific surface area of ​​the Si/C composite.

Benefits of technology

The uniform distribution of silicon nanoparticles on the surface of carbon-based particles is achieved, which reduces the generation of silicon carbides, improves the diffusion efficiency of lithium ion, extends the battery life and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode active material for a secondary battery, a method for preparing the same, and a lithium secondary battery including the same, the negative electrode active material including a silicon / carbon (Si / C) composite in which a silicon-based coating layer is formed on carbon-based particles, the peak area ratio A2 / A1 of the Si / C composite according to X-ray diffraction analysis is 0.2 to 3.0, and the peak area ratio A2 / A1 of the Si / C composite according to X-ray diffraction analysis is 0.2 to 3.0. The preparation method of the negative electrode active material for the secondary battery comprises the following steps: a pretreatment step of performing heat treatment on carbon-based particles; and a microwave calcination step of mixing the carbon-based particles and the silicon-based particles that have been subjected to the heat treatment and irradiating the mixture with microwaves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode active material for a secondary battery, a preparation method thereof and a lithium secondary battery comprising the negative electrode active material. Background Art

[0002] Recently, as the demand for electronic devices such as mobile devices has increased, the development of technologies for mobile devices has been launched. As driving power sources for these electronic devices, the demand for lithium secondary batteries such as lithium batteries, lithium ion batteries, and lithium ion polymer batteries has increased significantly. In addition, as automobile fuel consumption and exhaust-related regulations are being strengthened globally, the electric vehicle market is developing rapidly, and it is expected that the demand for medium and large secondary batteries such as secondary batteries for electric vehicles (EVs) and secondary batteries for energy storage devices (ESS) will increase rapidly.

[0003] On the other hand, as the demand for high capacity of secondary batteries such as medium and large secondary batteries is increasing, silicon-based negative electrode materials with excellent theoretical capacity are being studied as negative electrode materials for secondary batteries. However, silicon-based negative electrode materials cause large volume changes during the insertion / extraction of lithium, cause electrical desorption due to pulverization of silicon particles, and have the problem of reversible capacity loss during repeated charge and discharge cycles.

[0004] In order to solve the problem of mechanical damage to the electrode caused by the volume expansion and contraction of silicon and the resulting rapid shortening of life, research is being conducted to improve performance by combining it with a heterogeneous material that can buffer the volume expansion of silicon and by making silicon into nanoparticles. In particular, active development is being carried out in the technical aspects of the composite process for silicon (nano) particles and graphite and in the commercialization of the process cost reduction of silicon nanoparticle preparation.

[0005] The present invention relates to a method for preparing a composite negative electrode material of nano-sized silicon and a carbon-based material by a single process, which provides a method for preparing a silicon-carbon composite in which silicon nanoparticles are formed on a carbon surface by microwaves. The melting point of silicon is 1,414°C, and when it melts, its density increases more than that of a solid, similar to water. Graphite (carbon-based material) has the characteristic of rapidly generating heat when the π electrons present in the structure are alternately induced to negative (-) and positive (+) charges by microwaves (wavelength: 1m to 1mm; frequency: 300MHz to 300GHz). By applying this phenomenon, silicon with a lower melting point than graphite can be melt-processed on the graphite surface, and entropy can be rapidly increased by rapid energy transfer, so that a silicon nanomaterial (graphite of composite nano-silicon) with an increased specific surface area can be prepared on the graphite surface.

[0006] The method for preparing silicon-carbon composites using microwaves is a method that directly transfers energy to the carbon surface. Regardless of the medium that supports the carbon material, the temperature of the carbon itself will rise sharply as long as microwaves are irradiated, and will cool down rapidly after the microwave irradiation stops. Compared with existing heating methods, it has the advantage of reducing manufacturing time and energy costs.

[0007] However, since the energy is only transferred to the part irradiated with microwaves, there is a problem that silicon nanoparticles cannot be uniformly formed on the entire surface of carbon (graphite), or the attached silicon particles are coarsened and thinned. In this case, it is difficult to fully buffer the volume expansion of silicon particles during lithium insertion / extraction.

[0008] In addition, silicon carbide (SiC) synthesized at a high temperature of more than 900°C is generated as a byproduct on the surface of carbon (graphite) that is rapidly heated to about 1400°C by microwaves. This silicon carbide is inert to lithium ions and hinders the diffusion of lithium ions into silicon particles, resulting in problems of reduced capacity and efficiency. Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] The object of the present invention is to provide a Si / C composite prepared by a calcination process utilizing microwaves and a preparation method thereof, the technical feature of the above method being that the process of preparing silicon nanoparticles; and the process of composite silicon and carbon-based materials (Si / C composite) are carried out as a single process.

[0011] Another object of the present invention is to suppress the coarsening and thinning of silicon particles attached to the carbon surface by improving the microwave absorption capability of carbon (graphite), and to uniformly form silicon nanoparticles on the entire carbon surface.

[0012] In addition, another object of the present invention is to provide a Si / C composite having an improved initial charge / discharge capacity by suppressing the generation of silicon carbide (SiC) which is an inert material.

[0013] Means for solving technical problems

[0014] One embodiment of the present invention provides a negative electrode active material, comprising a silicon / carbon (Si / C) composite having a silicon-based coating formed on carbon-based particles, wherein the peak area ratio A2 / A1 of the Si / C composite according to X-ray diffraction analysis is 0.2 to 3.0. The A1 may be the area of ​​the Si peak in the X-ray diffraction analysis, and the A2 may be the area of ​​the SiC peak in the X-ray diffraction analysis.

[0015] The peak area ratio A2 / A1 of the Si / C composite according to X-ray diffraction analysis may be 0.3 to 0.5. A1 may be the area of ​​the Si peak in X-ray diffraction analysis, and A2 may be the area of ​​the SiC peak in X-ray diffraction analysis.

[0016] In the X-ray diffraction analysis method, the Si / C composite may have a Si peak area A1 of 2% to 7% and a SiC peak area A2 of 0.5% to 5.5% relative to 100% of the total peak area.

[0017] The BET specific surface area B2 of the Si / C composite can be 8 m 2 / g or above.

[0018] The BET specific surface area B2 of the Si / C composite can be 8 m 2 / g to 23m 2 / g.

[0019] The BET specific surface area ratio B2 / B1 of the Si / C composite may be greater than 1. B1 may be the BET specific surface area of ​​carbon-based particles before forming a silicon-based coating on the Si / C composite, and B2 may be the BET specific surface area of ​​the Si / C composite.

[0020] The BET specific surface area ratio B2 / B1 of the Si / C composite may be 1.2 to 2.5. B1 may be the BET specific surface area of ​​the carbon-based particles before the silicon-based coating is formed in the Si / C composite, and B2 may be the BET specific surface area of ​​the Si / C composite.

[0021] Relative to 100% of the total BET specific surface area B2 of the Si / C composite, the specific surface area contribution rate B2_C of the carbon-based particles may be 50% to 89.5%, and the specific surface area contribution rate B2_Si of the silicon-based coating may be 10.5% to 50%.

[0022] Relative to 100% of the total BET specific surface area B2 of the Si / C composite, the BET specific surface area contribution rate B2_C of the carbon-based particles may be 60% to 80%, and the BET specific surface area contribution rate B2_Si of the silicon-based coating may be 20% to 40%.

[0023] The silicon-based coating may include silicon nanoparticles having a size of 1 nm to 100 nm.

[0024] The silicon-based coating layer may be present in an amount of 5 wt % to 50 wt % relative to the total weight of the Si / C composite.

[0025] The above-mentioned silicon-based coating layer may be formed to have a thickness of 10 nm to 200 nm.

[0026] The carbon-based particles may be at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers, and hard carbon.

[0027] Colorimeter L of the above carbon-based particles * The value can be 35 or less.

[0028] Another embodiment of the present invention provides a method for preparing a negative electrode active material for a secondary battery, which includes: a pretreatment step of heat-treating carbon-based particles; and a microwave calcination step of mixing the heat-treated carbon-based particles and silicon-based particles and irradiating microwaves.

[0029] In the pretreatment step, the carbon-based particles may be heat-treated at 400° C. to 900° C. for 1 hour to 10 hours.

[0030] In the microwave calcination step, the surface of the heat-treated carbon-based particles can be quickly heated by microwaves, and the silicon-based particles are melted by the microwave-heated carbon-based particles to form a silicon-based coating on the surface of the carbon-based material.

[0031] The above-mentioned microwave heating can be achieved by irradiating microwaves at a power of 1 kW to 3 kW for 10 seconds to 10 minutes.

[0032] Still another embodiment of the present invention provides a negative electrode for a secondary battery, including the negative electrode active material.

[0033] Still another embodiment of the present invention provides a secondary battery including the negative electrode.

[0034] Effects of the Invention

[0035] In the present invention, by using pretreated carbon-based particles, the microwave absorption capacity can be improved by defects formed on the surface of the carbon-based particles. Uniform heating and rapid heating / cooling can be achieved on the carbon-based particles as a whole, so the residence time (maintenance time) within the temperature range (about 900° C.) where the SiC synthesis reaction occurs can be reduced, thereby reducing the amount of SiC synthesis.

[0036] In addition, in the present invention, the morphology of the molten silicon precipitated (attached) on the surface of the carbon-based particles can be controlled by the concave-convex structure (defects) on the surface of the pre-treated (heat-treated) carbon-based particles, thereby preventing the coarsening of the silicon particles and the connection (thin film formation) between the particles.

[0037] In addition, by controlling the BET specific surface area of ​​the Si / C composite within a specific range, silicon particles can be uniformly dispersed in nanometer size and attached to the surface of carbon-based particles. Therefore, the phenomenon of silicon particles being coarsened or attached in the form of a thin film can be prevented. As a result, the problem of electrolyte side reactions occurring due to excessive increase in specific surface area can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1a to Figure 1d Surface SEM images of the Si / C composites prepared in Comparative Example 1, Example 1, Example 2 and Example 3, respectively.

[0039] Figure 1e are SEM images of graphite particles before (left SEM image) and after (right SEM image) pretreatment according to Comparative Example 2.

[0040] Figure 2a to Figure 2d The X-ray diffraction (XRD) diagrams of the Si / C composites prepared in Comparative Example 1, Example 1, Example 2 and Example 3 are shown respectively.

[0041] Figure 3 This is a photograph showing hot spots formed on the surface of carbon-based particles by microwave irradiation (Microwave Chemical and Materials Processing Doi.org / 10.1007 / 978-981-10-6466-1_4). DETAILED DESCRIPTION

[0042] The advantages and features of the present invention and the methods for achieving them can be clearly seen through the accompanying drawings and the embodiments described in detail below. However, the present invention is not limited to the embodiments disclosed below, but can be implemented in various different forms. The embodiments are only used to fully disclose the present invention so that people with general knowledge in the technical field to which the present invention belongs can fully understand the scope of the invention. The scope of the present invention is determined by the claims of the present invention.

[0043] Unless otherwise specified, all terms (including technical and scientific terms) used in this specification can be used as the meanings that can be commonly understood by people with general knowledge in the technical field to which the present disclosure belongs. Throughout the specification, when a component is referred to as "including (or comprising)" an element, unless otherwise expressly provided, it is replaced by excluding any other elements, which may mean that a component may further include other elements. In addition, unless otherwise specified, nouns in the singular form also include plural forms.

[0044] One embodiment of the present invention provides a negative electrode active material, which includes a silicon / carbon (Si / C) composite having a silicon-based coating formed on carbon-based particles. In the present invention, by compounding with carbon-based particles that can buffer the volume expansion of silicon, the problem of mechanical damage to the electrode caused by the volume expansion and contraction of silicon and the resulting rapid shortening of life can be improved.

[0045] The peak area ratio A2 / A1 of the Si / C composite according to X-ray diffraction analysis may be 0.2 to 3.0, for example, 0.2 to 2.5, 0.2 to 2, 0.2 to 1.5, 0.2 to 1, 0.2 to 0.8, 0.2 to 0.7, 0.2 to 0.6, 0.3 to 0.6 or 0.3 to 0.5.

[0046] The above A1 is the peak area at all angles corresponding to the Si peak in the X-ray diffraction analysis method, and the above A2 is the peak area at all angles corresponding to the SiC peak in the X-ray diffraction analysis method. In addition, in the X-ray diffraction analysis method, all angles (2Theta) corresponding to the Si peak can be 28.4±0.5°, 47.3±0.5°, 56.1±0.5°, 69.1±0.5°, 76.4±0.5° and 88.0±0.5°, and each crystal plane can be (111), (202), (311), (400), (313) and (422), respectively. All angles (2Theta) corresponding to the SiC peak can be 35.6±0.5°, 41.4±0.5°, 59.9±0.5°, 71.7±0.5°, 75.5±0.5° and 89.9±0.5°, and each crystal plane can be (111), (020), (202), (311), (222) and (040), respectively. For reference, all angles equivalent to the graphite peak (2Theta) can be 26.5±0.5°, 42.3±0.5°, 44.5±0.5°, 50.6±0.5°, 54.6±0.5°, 59.8±0.5°, 71.4±0.5° and 77.4±0.5°, and each crystal plane can be (002), (100), (101), (012), (004), (013), (014) and (110).

[0047] If the peak area ratio is below the upper limit, the generation of silicon carbide (SiC) as an inert material can be suppressed, thereby increasing the ratio of silicon nanoparticles attached to the surface of carbon-based particles. If the peak area ratio is above the lower limit, the carbon-based particles and the solid silicon before melting are dispersed and uniformly mixed, so that the ratio of solid silicon melting on the carbon surface after microwave irradiation becomes higher and the ratio of unreacted silicon is reduced, which can mean that the preparation efficiency of Si / C composite is improved.

[0048] Silicon carbide (SiC) synthesized at a high temperature of more than 900° C. and inert to lithium ions can be attached to the surface of carbon particles that are rapidly heated to about 1400° C. by microwaves.

[0049] In the present invention, using pretreated carbon-based particles, the microwave absorption capacity of carbon-based particles can be improved by forming particle defects. The improvement of microwave absorption and heat generation performance can be confirmed by reducing the hot spot formation time on the carbon-based particle surface. In the present invention, by reducing the hot spot formation time, the carbon-based particles can be uniformly heated and quickly heated / cooled as a whole, so the residence time in the high temperature range where the SiC synthesis reaction occurs can be reduced. In addition, the morphology of the molten silicon can be controlled by the concavo-convex structure (defect) on the surface of the pretreated (heat-treated) carbon-based particles, so that the coarsening of silicon particles and the connection (thin filmization) between particles can be prevented. Therefore, the physical contact area between the silicon and carbon-based particles where the SiC synthesis reaction occurs can be reduced, so that the SiC synthesis amount can be further reduced.

[0050] On the other hand, in the present invention, as for the hot spots of carbon-based particles, when microwaves are irradiated to carbon-based particles, a uniform reaction does not occur at all locations at the same time, but a reaction occurs first at a specific location, and this phenomenon can be defined as a "hot spot". The hot spots appearing on the surface of the carbon-based particles can be observed with the naked eye, and the "hot spot time" can be measured based on the time when the reaction first occurs.

[0051] In the X-ray diffraction analysis method, the Si peak area A1 of the above-mentioned Si / C composite relative to the total peak area of ​​100% can be 2% to 7%, for example, 2.5% to 7%, 2.5% to 6.5%, 2.5% to 6%, 2.5% to 5.5%, 2.5% to 5%, or 2.5% to 4%. In addition, the SiC peak area A2 relative to the total peak area of ​​100% can be 0.5% to 5.5%, 0.5% to 5%, 1% to 5%, 2% to 5%, 3% to 5%, 3.5% to 5%, 3.5% to 4.5%, or 4% to 4.5%. Therefore, the above-mentioned effect can be further improved.

[0052] On the other hand, 100% of the total peak area may refer to the sum of the peak area A1 at all angles corresponding to the Si peak, the peak area A2 at all angles corresponding to the SiC peak, and the peak area A3 at all angles corresponding to the graphite peak.

[0053] The BET specific surface area B2 of the Si / C composite can be 8 m 2 / g or more, for example, 8m 2 / g to 23m 2 / g, 8m 2 / g to 20m2 / g, 8m 2 / g to 17m 2 / g, 8m 2 / g to 15m 2 / g, 8m 2 / g to 14m 2 / g, 8m 2 / g to 13m 2 / g, 9m 2 / g to 13m 2 / g or 9m 2 / g to 12m 2 / g.

[0054] When using microwaves to prepare silicon-carbon composites, silicon is only attached to the surface of carbon-based particles heated by microwave irradiation. Therefore, according to analysis, the silicon melted by the microwave combustion reaction does not block the concave-convex structure and pore structure of the pretreated carbon-based particle surface. It can be confirmed that the BET specific surface area of ​​the Si / C composite finally prepared after the microwave calcination reaction can be adjusted to a higher level than before the reaction. On the other hand, if the above-mentioned BET specific surface area falls within the above-mentioned range, it may mean that the silicon particles are uniformly dispersed in nanometer size and attached to the surface of the carbon-based particles. If the above-mentioned BET specific surface area is less than the lower limit, it means that thin film silicon particles are attached. If the above-mentioned BET specific surface area exceeds the upper limit, the particle structure collapses, exposing the basal surface of the graphite, thereby, the electrolyte side reaction may be caused due to excessive increase in specific surface area.

[0055] The BET specific surface area B2 / B1 of the Si / C composite may be 1 or more, for example, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, or 1.5 or more and 2.5 or less, 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, or 2.0 or less. The B1 is the BET specific surface area of ​​the carbon-based particles before the silicon-based coating is formed in the Si / C composite, and the B2 is the BET specific surface area of ​​the Si / C composite (after the silicon-based coating is formed).

[0056] If the above-mentioned BET specific surface area ratio B2 / B1 is above the lower limit value, the ratio of molten silicon attached to the surface of the carbon-based particles after microwave irradiation in the form of nanoparticles increases, which may mean controlling (preventing) the coarsening of silicon particles and the connection between particles (thin film formation). On the other hand, when the particle size of silicon attached to the surface of carbon-based particles increases or silicon particles are connected to form a thin film (network morphology), the BET specific surface area may be reduced due to the silicon coating. In addition, when the above-mentioned BET specific surface area ratio B2 / B1 is below the upper limit value, the melting ratio of solid silicon on the surface of microwave-irradiated carbon-based particles is high and the ratio of unreacted silicon is low, which may mean that the preparation efficiency of Si / C composites is improved as a whole.

[0057] In the above-mentioned Si / C composite, relative to the total BET specific surface area B2 of 100%, the specific surface area contribution rate B2_C of the above-mentioned carbon-based particles can be 50% to 89.5%, and the specific surface area contribution rate B2_Si of the above-mentioned silicon-based coating can be 10.5% to 50%. Among them, the specific surface area contribution rate B2_C of the above-mentioned carbon-based particles refers to the BET specific surface area of ​​graphite (pretreated graphite) that has been subjected to microwave treatment in the same manner except that silicon powder is not used, and its percentage relative to the BET specific surface area of ​​the Si / C composite is calculated by measuring it. The specific surface area contribution rate B2_Si of the above-mentioned silicon coating refers to the value obtained by subtracting the specific surface area ratio of the above-mentioned carbon-based particles from the BET specific surface area of ​​the entire Si / C composite of 100%.

[0058] For example, in the above-mentioned Si / C composite, relative to 100% of the total BET specific surface area B2, the contribution rate B2_C of the above-mentioned carbon-based particles can be 50% to 85%, 55% to 80%, 60% to 80% or 65% to 75%, and the contribution rate B2_Si of the above-mentioned silicon coating can be 15% to 50%, 20% to 45%, 20% to 40% or 25% to 35%.

[0059] As the contribution rate B2_Si of the silicon coating increases and the contribution rate B2_C of the carbon-based particles decreases, the ratio of molten silicon attached to the surface of the carbon-based particles after microwave irradiation in the form of nanoparticles may increase. On the contrary, as the contribution rate B2_Si of the silicon coating decreases and the contribution rate B2_C of the carbon-based particles increases, the increase in the total BET specific surface area may be due to the change in the morphology of the surface of the carbon-based particles after microwave irradiation, and this means that unreacted silicon increases.

[0060] The carbon-based particles may be at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers and hard carbon, for example, preferably natural graphite or artificial graphite. In addition, the carbon-based particles may be single particles or secondary particles formed by aggregation of multiple particles.

[0061] In addition, the average particle size D50 of the above-mentioned carbon-based particles can be 5μm to 30μm, 5μm to 20μm or 10μm to 20μm, the average particle size D10 can be 3μm to 20μm, 3μm to 15μm or 5μm to 15μm and / or the average particle size D90 can be 15μm to 35μm, 15μm to 30μm or 20μm to 25μm.

[0062] In addition, the above-mentioned carbon-based particles can be spherical, plate-shaped, or needle-shaped particles. Like plate-shaped and needle-shaped particles, the propagation path of microwaves can be expanded by adjusting the material structure (porous, hollow, core-shell, multi-layer and hierarchical), thereby further improving the absorption capacity of the microwave absorber.

[0063] The conditions for controlling the heating of carbon-based particles by microwaves include the type, content and particle shape of the carbon material. If the type, average particle size and morphology of the carbon-based particles fall within the scope of the present invention described above, the microwave absorption capacity can be improved.

[0064] Colorimeter L of the above carbon-based particles * The value can be below 35, for example, the colorimeter L * The value may be 34 or less, 33 or less, or 32 or less. The lower limit value is not particularly limited, and may be, for example, 10 or more, 20 or more, 25 or more, or 30 or more.

[0065] The term "colorimeter" used in the present invention * )) value" may refer to the value of * a * b * The L value represents the lightness in the chromaticity coordinates of the above-mentioned L value ranges from 0 to 100, and the closer to 0, the closer to black, and the closer to 100, the closer to white. In the present invention, the heat-treated carbon-based particles increase light absorption due to surface defects, so that the colorimeter L * The value may be reduced. When the color difference meter L of the above carbon-based particles * When the value is within the design range, the heat generation performance of the carbon-based particles is improved by forming defects on the surface of the heat-treated carbon-based particles, and the morphology formation of the molten silicon is controlled by the concave-convex structure (defects) on the surface of the heat-treated carbon-based particles, thereby preventing the coarsening of the silicon particles and the connection between the silicon particles (thin film formation).

[0066] On the other hand, there is no limitation on the device used for measuring the above colorimeter, but for example, devices such as a spectrophotometer, a colorimeter, a colorimeter, a color identifier, and a color illuminance meter can be used. For example, the above colorimeter can be measured using a colorimeter (Chromameter) CR-410 KONIKA MINOLTA.

[0067] The above-mentioned silicon-based coating may include silicon (Si) particles having a size of 10nm to 100nm. Specifically, the particle size D50 of the silicon nanoparticles contained in the above-mentioned silicon-based coating may be 10nm to 100nm or 20nm to 100nm. In the present invention, by using pre-treated carbon-based particles having a concavo-convex structure (defect) formed on the surface, the morphology of the molten silicon on the particle surface can be controlled. As a result, the coarsening of silicon particles and the connection (thin filmization) between particles can be prevented.

[0068] On the other hand, the size of the silicon particles can refer to the size (D50) measured by cumulative volume. In this specification, unless otherwise defined, D50 refers to the average size of the diameter of the pores representing a cumulative volume of 50% by volume in the particle size distribution. The average size D50 can be measured by methods known to those skilled in the art, for example, it can be measured using a transmission electron microscope (Transmission Electron Microscope) photo or a scanning electron microscope (Scanning Electron Microscope) photo. As another method, it can be measured by using a measuring device using a dynamic light scattering method, performing data analysis, counting the number of pores in each pore size range, and thus calculating the average size D50 value.

[0069] The content of the silicon-based coating layer may be 1 wt % to 50 wt %, for example, 1 wt % to 40 wt %, 1 wt % to 30 wt %, 5 wt % to 30 wt %, or 5 wt % to 20 wt %, relative to the total weight of the Si / C composite. In addition, the silicon-based coating layer may be formed to have a thickness of 10 nm to 200 nm, for example, 10 nm to 180 nm, 10 nm to 160 nm, 10 nm to 150 nm, or 10 nm to 130 nm.

[0070] The Si / C composite may further include a carbon coating on the silicon coating. By minimizing direct exposure of silicon in the silicon-based coating to the electrolyte, electrolyte side reactions can be reduced, and the volume expansion of silicon particles can be further buffered, thereby improving the life characteristics of the battery. The carbon coating may be formed to have a thickness of 0.01 μm or more, for example, may be formed to have a thickness of 0.03 μm or more or 0.05 μm or more and 10 μm or less, 5 μm or less, or 1 μm or less. Thus, the above effects can be further improved.

[0071] Next, a method for preparing a negative electrode active material for a secondary battery is provided, which may be the method for preparing the negative electrode active material according to one embodiment of the present invention.

[0072] The method for preparing the negative electrode active material for a secondary battery comprises: a pretreatment step of heat-treating carbon-based particles; and a microwave calcination step of mixing the heat-treated carbon-based particles with silicon-based particles and irradiating microwaves.

[0073] The above-mentioned pretreatment step is a step of heat-treating the carbon-based particles at 400°C to 900°C for 1 hour to 10 hours. The purpose is to improve the heat generation performance of the carbon-based particles in the calcination step of irradiating microwaves by forming defects on the surface of the carbon-based particles. The heat generation performance of the carbon-based particles can be improved by forming defects on the surface of the heat-treated carbon-based particles. For example, the above-mentioned pretreatment step can be achieved by heat-treating for 1 hour to 6 hours, 2 hours to 6 hours or 3 hours to 6 hours in an air atmosphere at a heating rate of 1°C / min to 10°C / min or 2°C / min to 7°C / min and a reactor temperature of 400°C to 800°C, 400°C to 700°C or 400°C to 600°C.

[0074] The above-mentioned pretreatment step is a step of heat-treating the carbon-based particles, characterized in that the heat treatment is performed so that the weight reduction rate of the carbon-based particles before and after the heat treatment (weight of the carbon-based particles after heat treatment / weight of the carbon-based particles before heat treatment×100(%)) is greater than 1 weight % and less than 40 weight %, greater than 5 weight % and less than 30 weight %, greater than 10 weight % and less than 25 weight %, greater than 14 weight % and less than 25 weight %, or greater than 15 weight % and less than 20 weight %.

[0075] The above-mentioned calcination step is a step of mixing the heat-treated carbon-based particles and the silicon-based particles to obtain a mixture in which the silicon-based particles are dispersed on the surface of the carbon-based particles, rapidly heating the heat-treated carbon-based particles in the above-mentioned mixture with microwaves, and melting the silicon-based particles by rapidly heating the carbon-based particles with microwaves, thereby forming a silicon-based coating on the surface of the carbon-based material.

[0076] The mixing may be performed using a particle mixer at 500 to 2,000 RPM or 700 to 1,500 RPM for 1 to 10 minutes. As the particle mixer, a self-rotating mixer, a revolving mixer, a blade mixer, or a particle fusion machine may be used, but the present invention is not limited thereto.

[0077] In addition, as for the above-mentioned mixing, the mixing may be performed by mixing the carbon-based particles and the silicon-based particles at a weight ratio of 99:1 to 60:40, 99:1 to 70:30, 95:5 to 70:30, or 95:5 to 80:20.

[0078] The carbon-based particles may be natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers, hard carbon or a combination thereof, and the silicon-based particles may be silicon particle powder having a size of 10 nm to 10 μm, 100 nm to 10 μm or 100 nm to 5 μm.

[0079] The microwave heating may be irradiating microwaves (wavelength: 1m to 1mm; frequency: 300MHz to 300GHz) at a power of 1kW to 3kW for 10 seconds to 10 minutes, 30 seconds to 2 minutes, or 30 seconds to 60 seconds. In addition, the microwave heating may heat the surface of the carbon-based particles to above 1,400°C within 1 minute, for example, the surface of the carbon-based particles may be heated to above 1,400°C within 30 seconds or within 10 seconds. When microwaves are irradiated to the heat-treated carbon-based particles, the microwave absorption performance and the heat generation performance are improved by forming defects on the surface of the heat-treated carbon-based particles, thereby shortening the formation time of hot spots on the particle surface. In the present invention, the hot spot formation time may be shortened to 5 seconds to 30 seconds, 5 seconds to 25 seconds, 5 seconds to 20 seconds, 10 seconds to 20 seconds, or 10 seconds to 15 seconds. On the other hand, referring to Figure 3 "Hotspot" refers to the phenomenon that due to the nature of microwaves (MW), when MW is irradiated, the reaction does not occur equally in all areas, but occurs partially first. In this patent, it refers to the phenomenon that heat is observed first. On the other hand, as a method of measuring the hotspot time, such as Figure 3 As shown, the time when the heating part is observed with the naked eye is measured. In the present invention, since defects are formed on the surface of the pretreated graphite particles, the microwave absorption capacity can be improved. Therefore, since the surface heating characteristics of the carbon particles are improved when microwave irradiated, the time for observing the heating phenomenon can be shortened.

[0080] After the microwave calcination step, a cooling step may be further included to prevent the crystallinity of the silicon-based material attached to the surface from increasing due to the heat energy remaining in the carbon-based particles. The cooling step may be performed at room temperature or at a temperature of -10°C to 10°C and at normal pressure, preferably in a cooled reactor injected with nitrogen.

[0081] Still another embodiment of the present invention provides a negative electrode for a secondary battery and a secondary battery including the negative electrode active material.

[0082] The negative electrode includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and the negative electrode active material according to one aspect of the present invention is present in the negative electrode active material layer.

[0083] There is no particular limitation on the negative electrode current collector, as long as it has conductivity without causing chemical changes in the battery, and examples thereof may include stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. In addition, the negative electrode current collector may generally have a thickness of 3 μm to 500 μm, or may increase the binding force of the negative electrode active material by forming tiny concave-convex shapes on the surface of the current collector. For example, the negative electrode current collector may be provided in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven body, etc.

[0084] The negative electrode active material layer may be a layer containing the above-mentioned negative electrode active material, a conductive material and a binder.

[0085] The above-mentioned conductive material is used to impart conductivity to the electrode, and can be used without restriction as long as it does not cause chemical changes in the negative electrode active material and has conductivity. Non-limiting examples of conductive materials include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. Typically, the content of the conductive material can be 1% to 30% by weight based on the total weight of the negative electrode active material layer.

[0086] The above-mentioned binder is a material that plays a role in improving the adhesion between multiple negative electrode active material particles and the bonding force between the negative electrode active material and the current collector. Non-limiting examples of binders include: polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers. Generally, the content of the binder can be 1% to 30% by weight relative to the total weight of the negative electrode active material layer.

[0087] In addition to using the above-mentioned negative electrode active material, the negative electrode according to one embodiment of the present invention can be prepared according to a conventional method for preparing a negative electrode for a secondary battery. For example, the negative electrode can be prepared by applying a slurry for forming a negative electrode active material layer to a negative electrode collector, and then drying and rolling it, wherein the slurry includes a negative electrode active material and a selective binder and a conductive material. According to another example, the negative electrode can be prepared by casting a slurry for forming a negative electrode active material layer on a separate carrier, and then laminating a thin film obtained by stripping the negative electrode active material layer from the carrier on the negative electrode collector.

[0088] According to another aspect of the present invention, an electrochemical device comprising the above negative electrode is provided, wherein the electrochemical device may be a battery, a capacitor, etc., more specifically, a lithium secondary battery.

[0089] The secondary battery includes a negative electrode, a positive electrode positioned opposite to the negative electrode, and a separator and an electrolyte (electrolyte) between the negative electrode and the positive electrode. In addition, the lithium secondary battery may include a battery container (housing) that accommodates an electrode assembly including a positive electrode, a negative electrode and a separator, and a sealing member that seals the battery container.

[0090] Among them, according to the shape of the battery container (shell), lithium secondary batteries can be divided into can-type lithium secondary batteries and pouch-type lithium secondary batteries. The above-mentioned can-type lithium secondary batteries have a can form in which the electrode assembly is enclosed in a metal can, and the above-mentioned pouch-type lithium secondary batteries have a pouch form in which the electrode assembly is enclosed in a bag made of a sheet material such as an aluminum laminate.

[0091] Hereinafter, the present invention will be described in more detail with reference to examples, however, these examples are only used to illustrate the present invention in more detail, and the scope of the present invention should not be construed as being limited to the following examples.

[0092] Example

[0093] Preparation Example 1. Preparation of Si / C composite negative electrode active material

[0094] <Examples 1 to 3 and Comparative Example 1>

[0095] Step 1: Graphite Pretreatment

[0096] 20 g of natural graphite (D50: 15 μm) was weighed into a crucible and then placed in a tube furnace. Pretreated graphite was obtained by heat treatment at 560°C for 1 to 5 hours under the conditions of a heating rate of 5°C / min and an air atmosphere. The weight reduction rate of the pretreated graphite relative to the graphite before pretreatment is shown in Table 1 below.

[0097] (Heat treatment time = Example 1: 1 hour, Example 2: 4 hours, Example 3: 5 hours, Comparative Example 1: no heat treatment, Comparative Example 2: 7 hours)

[0098] Step 2: Si / C composite by microwave irradiation

[0099] The pre-treated natural graphite and plate-like silicon particles (D50: 400 nm) powder were charged into a super mixer at a weight ratio of 9:1 and mixed at 1,000 RPM for 10 minutes. Next, 2,450 MHz microwaves were irradiated at a power condition of 1 kW for 60 seconds. At this time, the hot spot formation time is shown in Table 1 below.

[0100] Next, cooling was performed at a rate of -5°C / min to prepare a Si / C composite negative electrode active material having a silicon coating layer formed on the pretreated natural graphite.

[0101] The hotspot formation time is the time measured when the reaction (hotspot) first appears on the surface of the carbon-based particles, such as Figure 3 The results shown reflect observations made with the naked eye.

[0102] Table 1

[0103]

[0104] Preparation Example 2. Preparation of lithium secondary battery

[0105] A negative electrode slurry was prepared by dispersing 30 g of 96 wt % of the prepared negative electrode active material, 1 wt % of carbon black, 1.5 wt % of SBR binder and 1.5 wt % of carboxymethyl cellulose in distilled water. The prepared negative electrode slurry was uniformly coated on a copper film and vacuum dried at 135° C. to prepare a negative electrode for a lithium secondary battery.

[0106] 94 wt% LiNi 0.9 Co 0.1 Mn 0.1 O2 (NCM911, EcoPro BM), 3 wt% carbon black and 3 wt% PVdF binder were mixed in N-methyl-2-pyrrolidone to prepare positive electrode slurry. The prepared positive electrode slurry was evenly coated on an aluminum film, vacuum dried at 135°C, and then rolled to prepare a positive electrode for a lithium secondary battery.

[0107] The prepared positive and negative electrodes and a porous polyethylene film (Celgard 2300, thickness: 25 μm) separator were placed in a battery container, and a lithium secondary battery was manufactured using an electrolyte containing LiPF6 at a concentration of 1.15 M in a solvent mixed with EC:EMC at a volume ratio of 3:7.

[0108] Experimental example

[0109] Experimental Example 1. Confirmation of the shape of the silicon coating on the surface of carbon particles by SEM image analysis

[0110] Figure 1a to Figure 1d Surface SEM images of Si / C composite particles prepared in Comparative Example 1 and Examples 1 to 3, respectively.

[0111] Reference Figure 1a to Figure 1d It can be confirmed that in the Si / C composites prepared in Examples 1 to 3, silicon nanoparticles with a size of 1 nm to 100 nm are uniformly attached to the graphite surface. In particular, it is found that the deposition ratio of spherical silicon nanoparticles on the graphite surface increases as the graphite weight reduction rate and the graphite heat treatment time increase within the preferred range. On the other hand, in the case of Comparative Example 1, it is confirmed that the deposition morphology and size of silicon are not uniform due to the coarsening of the silicon particle size and the connection structure (network structure) between the particles.

[0112] Experimental Example 2. Carbon-based particle properties and surface properties of Si / C composites according to heat treatment conditions of carbon-based particles evaluate

[0113] The BET specific surface areas of the Si / C composites prepared in Comparative Examples 1 and 2 and Examples 1 to 3 were measured using the BET method, and the results are summarized in Table 2 below.

[0114] In the following Table 2, "pretreated graphite B1" refers to the BET specific surface area value of the pretreated graphite (graphite before the silicon-based coating is formed in the Si / C composite) prepared in step 1. "Si / C composite B2" refers to the BET specific surface area value of the Si / C composite prepared in step 2. "Microwave-treated graphite R" refers to the BET specific surface area value of microwave-treated (pretreated) graphite prepared in the same manner as step 2 (microwave irradiation) except that silicon powder is not used.

[0115] The specific surface area ratio B2 / B1 refers to a value calculated by calculating the BET specific surface area B2 of the Si / C composite after forming the silicon-based coating relative to the BET specific surface area B1 of the carbon-based particles before forming the silicon-based coating.

[0116] The specific surface area ratio B2 / R refers to the value calculated as the ratio of the BET specific surface area B2 of the above-mentioned Si / C composite after forming the silicon-based coating relative to the BET specific surface area R of microwave-treated (pre-treated) graphite prepared in the same manner as step 2 (microwave irradiation) except that no silicon powder is used.

[0117] The specific surface area contribution rate B2_C refers to the percentage of the BET specific surface area of ​​the microwave-treated graphite (pretreated graphite) calculated after measuring the BET specific surface area of ​​the microwave-treated graphite in the same manner except that no silicon powder is used, relative to the BET specific surface area of ​​the Si / C composite. Specifically, it refers to the value calculated as the percentage of the BET specific surface area R of the microwave-treated graphite relative to the BET specific surface area B2 of the Si / C composite.

[0118] Table 2

[0119]

[0120] Referring to Table 2, compared with Comparative Example 1, the BET specific surface area B2 of the Si / C composites prepared in all examples increased to 9.5 m 2 / g, as the graphite weight reduction rate and the graphite heat treatment time increase within the preferred range, the BET specific surface area tends to increase.

[0121] In the case of the specific surface area ratio B2 / B1, the specific surface area ratio of Comparative Example 1 is the highest at 2.7 m 2 / g, and a decreasing trend was observed with the increase of graphite weight reduction rate (Example 1 → Comparative Example 2).

[0122] In the case of the specific surface area contribution rate B2_C, the specific surface area contribution rates of Comparative Examples 1 and 2 are relatively high. In the examples, as the graphite weight reduction rate increases (Example 1 → Example 3), it shows a decreasing tendency. In particular, in Examples 2 to 3, it is confirmed that the specific surface area contribution rate B2_C of carbon is significantly reduced compared with Comparative Examples 1, 2 and Example 1.

[0123] When graphite without pretreatment is used (Comparative Example 1), the ratio of the increase in specific surface area by microwave calcination due to the change in the graphite surface morphology is higher than that of the embodiment, and therefore, it is analyzed that the unreacted silicon is relatively increased in Comparative Example 1. In addition, it is analyzed that since the total BET specific surface area B2 of the Si / C composite in Comparative Example 1 is significantly smaller than that of the embodiment, the ratio of coarsening of silicon particles and attachment in the form of inter-particle connection is higher.

[0124] On the contrary, it was analyzed that when pre-treated graphite was used (Examples 1 to 3), the heat generation performance could be improved and the morphology of silicon melt could be controlled by the surface defects of carbon-based particles, so the rate of silicon attachment in the form of nanoparticles increased. These analysis results are consistent with Figure 1a to Figure 1d The SEM images are consistent.

[0125] on the other hand, Figure 1e : are SEM images of graphite particles before (left SEM image) and after (right SEM image) pretreatment according to Comparative Example 2. Figure 1eAs shown in Table 2, when the weight reduction rate of the pretreated graphite reaches 40%, the particle structure collapses and the heat generation performance is excessively improved, resulting in an increase in the SiC crystal phase and an increase in the ratio of silicon deposited in the form of a thin film, so the BET increase rate shows a downward trend.

[0126] Experimental Example 3. XRD Analysis of Si / C Composite and Evaluation of Electrochemical Performance of Lithium Secondary Battery

[0127] XRD analysis was performed using Bruker's D8 ADVANCE A25 and measured by applying a current of 30 mA at a voltage of 45 kV. For the analysis of each phase, COD No. 4104917 (Si), 1011031 (SiC), and 9011577 (graphite) were used for comparison. The results confirmed all peak positions corresponding to each crystalline phase. The peak information for each crystalline phase is shown in Table 3 below.

[0128] By analyzing the peaks obtained in this way ( Figure 2a to Figure 2d ) were deconvolved to obtain the peak area A1 (%) corresponding to Si and the peak area A2 (%) corresponding to SiC. The measurement results are shown in Table 4 below.

[0129] As for the electrochemical performance analysis, an electrochemical analyzer (Shincorp, Toscat-3100) was used to perform charge and discharge experiments at 25° C. with a voltage range of 0.005 V to 1.5 V and a C rate of 0.1 C to 0.5 C to measure the initial charge capacity, initial discharge capacity, and initial efficiency (ICE). The measurement results are shown in Table 4 below.

[0130] Table 3

[0131]

[0132] Table 4

[0133]

[0134] Referring to Table 4, it was confirmed that in the case of the lithium secondary batteries manufactured in Examples 1 to 3, when heat-treated graphite was applied, the generation of SiC as an inert material was suppressed, thereby improving the charge / discharge capacity and the initial efficiency.

[0135] On the other hand, it was analyzed that in the case of Comparative Example 2, when excessively pretreated graphite was used, the particle structure collapsed, exposing the basal plane of graphite, and as a result, the initial coulombic efficiency decreased due to excessive electrolyte exposure.

[0136] As described above, although the present invention has been illustrated and described with respect to specific embodiments, it is obvious to those skilled in the art that various modifications and changes can be made to the present invention without departing from the technical concept of the present invention provided in the appended claims.

Claims

1. A negative electrode active material for a secondary battery, characterized in that: A silicon / carbon (Si / C) composite having a silicon-based coating formed on carbon-based particles, wherein the peak area ratio A2 / A1 of the Si / C composite according to an X-ray diffraction analysis method is 0.2 to 3.0, wherein A1 is the area of ​​the Si peak in the X-ray diffraction analysis method, and A2 is the area of ​​the SiC peak in the X-ray diffraction analysis method.

2. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The peak area ratio A2 / A1 of the Si / C composite according to X-ray diffraction analysis is 0.3 to 0.5, wherein A1 is the area of ​​the Si peak in the X-ray diffraction analysis, and A2 is the area of ​​the SiC peak in the X-ray diffraction analysis.

3. The negative electrode active material for a secondary battery according to claim 1, characterized in that: In an X-ray diffraction analysis method, the Si / C composite has a Si peak area A1 of 2% to 7% and a SiC peak area A2 of 0.5% to 5.5% relative to 100% of the total peak area.

4. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The BET specific surface area B2 of the Si / C composite is 8 m 2 / g or above.

5. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The BET specific surface area B2 of the Si / C composite is 8 m 2 / g to 23m 2 / g.

6. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The BET specific surface area ratio B2 / B1 of the Si / C composite is greater than 1, wherein B1 is the BET specific surface area of ​​the carbon-based particles before the silicon-based coating is formed in the Si / C composite, and B2 is the BET specific surface area of ​​the Si / C composite.

7. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The BET specific surface area ratio B2 / B1 of the Si / C composite is 1.2 to 2.5, wherein B1 is the BET specific surface area of ​​the carbon-based particles before the silicon-based coating is formed in the Si / C composite, and B2 is the BET specific surface area of ​​the Si / C composite.

8. The negative electrode active material for a secondary battery according to claim 1, characterized in that: Relative to 100% of the total BET specific surface area B2 of the Si / C composite, the BET specific surface area contribution rate B2_C of the carbon-based particles is 50% to 89.5%, and the BET specific surface area contribution rate B2_Si of the silicon-based coating is 10.5% to 50%.

9. The negative electrode active material for a secondary battery according to claim 1, characterized in that: Relative to 100% of the total BET specific surface area B2 of the Si / C composite, the BET specific surface area contribution rate B2_C of the carbon-based particles is 60% to 80%, and the BET specific surface area contribution rate B2_Si of the silicon-based coating is 20% to 40%.

10. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The silicon-based coating includes silicon nanoparticles with a size of 1 nm to 100 nm.

11. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The content of the silicon-based coating layer is 5 wt % to 50 wt % relative to the total weight of the Si / C composite.

12. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The silicon-based coating layer is formed to have a thickness of 10 nm to 200 nm.

13. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The carbon-based particles are at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers and hard carbon.

14. The negative electrode active material for a secondary battery according to claim 1, characterized in that: Colorimeter L of the carbon-based particles * The value is below 35.

15. A method for preparing a negative electrode active material for a secondary battery, characterized in that: include: a pretreatment step, heat treating the carbon-based particles; and The microwave calcination step is to mix the heat-treated carbon-based particles and silicon-based particles and irradiate microwaves.

16. The method for preparing a negative electrode active material for a secondary battery according to claim 15, characterized in that: In the pretreatment step, the carbon-based particles are heat-treated at 400° C. to 900° C. for 1 hour to 10 hours.

17. The method for preparing a negative electrode active material for a secondary battery according to claim 15, characterized in that: In the microwave calcination step, the surfaces of the heat-treated carbon-based particles are rapidly heated by microwaves, and the silicon-based particles are melted due to the carbon-based particles being heated by microwaves to form a silicon-based coating on the surface of the carbon-based material.

18. The method for preparing a negative electrode active material for a secondary battery according to claim 15, characterized in that: The microwave heating is achieved by irradiating microwaves at a power of 1 kW to 3 kW for 10 seconds to 10 minutes.

19. A negative electrode for a secondary battery, characterized in that: The negative electrode active material according to claim 1 is included.

20. A secondary battery, characterized in that: Includes the negative electrode according to claim 19.